PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARIR BERBASIS WEB - yeka hendriyani; Ambiyar Ambiyar; Ika Parma Dewi (Jurnal Informatika: Jurnal Pengembangan IT, 2020)
This research aims to design a Decision Support System (DSS) to choose a job with web base. So that later this system can be a container consulting user or meember in determining the choice of type of work in accordance with the personality they have. The input data used is the result of personality tests then the data will be processed using Case Based Reasoning (CBR) method to be matched with the psychological value of personality then matched to the type of work then the system will give advice job vacancy according to his personality. The design of this system using structured system design model as data flow and object-based system design is Unified Modeling Language (UML), PHP as programming language with Codeigniter faramework, and MySQL as database. The results of this study is an application that can be used by the community to consult in determining the appropriate job type choices.